Adipose Tissue-Secreted Factors Alter Bladder Cancer Cell Migration - Nisha Hariharan; Keith A. Ashcraft; Robert S. Svatek; Carolina B. Livi; Desiree Wilson; Dharam Kaushik; Robin J. Leach; Teresa L. Johnson-Pais (Hindawi Limited, 2018)
Background. Obesity is associated with an increased risk of bladder cancer recurrence. This study investigated the role of adipose tissue in bladder cancer progression. Methods. Gene expression profiling was performed on adipose tissues collected from normal weight (n=5), overweight (n=11), and obese (n=10) patients with invasive bladder cancer, and adipose stromal cells (ASCs) were obtained from two normal weight, two overweight, and two obese patients. Conditioned media (CM) was characterized and evaluated for its effects on the proliferation, migration, and invasive potential of T24 bladder cancer cells. Results. Expression profiling demonstrated depot-specific or body mass index-specific differences. Increased T24 cell migration was observed using CM harvested from all ASCs. ASC CM from an obese patient significantly increased T24 cell migration and invasion compared to ASC CM collected from normal weight and overweight patients. We identified abundant expression of CXCL1, PAI1, IL6, CX3CL1, and CCL2 in all CM. Exogenous treatment of T24 cells with PAI1, IL6, and CXCL1 enhanced migration. Depletion of CXCL1, PAI1, and IL6 in an obese patient ASC CM abrogated T24 migration. Conclusion. Factors secreted by adipose tissue influence the migration of bladder tumor cells and could play an active role in tumor progression.